How digital competency for Indonesian TVET educators explored in the last decade: a systematic literature review based on the Australian qualification framework - Widaningsih, L; Sari, A.R.; Dwiyanti, V; Maknun, J; Hayat, Jasmine (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
Indonesia's National Qualification Framework (KKNI) was adopted from the Australian Qualification Framework (AQF). However, there is still no certification scheme in digital competency for educators, despite the growing urgency of having digitally capable teachers in the Industrial Revolution 4.0. The aim of the study is to explore how digital competency among Indonesian TVET educators has been researched in the last ten years. The study used a Systematic Literature Review using the PRISMA Framework, and the data source was taken from reputable scientific journals indexed by Scopus and SINTA as well as formal reports issued by the government. The competencies required in Digital Education for Educators based on the AQF were used to derive keywords that were divided into three categories. The ongoing result shows that digital competencies were widely researched. However, unlike the AQF standard that uses foundation skills, the basis of digital competency among TVET educators in Indonesia is still unclear. In addition, the literature on the related topics is still integrated and used in the policy to improve the digital qualification among educators. The result of this research can contribute to the importance of adding digital competency certification for TVET educators in Indonesia's National Qualification Framework (KKNI).